Pre-service English Teachers' Perceptions of Autonomous Learning - Bhandari , Bhim Lal (Spandan, 2024)
This study aims to explore pre-service English teachers' perceptions of autonomous language learning. For this study, we applied Vygotsky's (1896-1934) socio-cultural theory as a theoretical framework and narrative inquiry research design to explore our participants' stories regarding their perceptions and activities they were involved into develop autonomous language learning. We selected. Four M.Ed. pre-service English teachers majoring in English from two constituent campuses of Tribhuvan University, Nepal located in the Rupandehi district purposively. We interviewed them using a semi-structured in-depth interview to elicit the relevant information. The study revealed that the pre-service English teachers' perception of autonomous learning was positive. They were found participating in autonomous activities in and outside the classroom. They used libraries to read authentic texts, listened to and watched audio-visual materials and used internet resources to maximize their autonomy in learning English. The study can contribute to a better understanding of pre-service English teachers' autonomy to get insightful ideas to enhance their autonomy shifting from teaching culture to learning culture.